CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) support to the revision of the SADC (Southern African Development Community) Climate Change Strategy and Action Plan - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
Through SADC Secretariat’s climate change expert group, CCAFS contributed directly to the revision of the SADC Climate Change Strategy and Action Plan (2020-2030) with respect to agriculture, gender and youth